2002
DOI: 10.1067/mva.2002.124371
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein (a) in patients with aortic aneurysmal disease

Abstract: The lipoprotein (a) serum level, an indicator of atherosclerosis, is significantly elevated in patients with abdominal aneurysms independently of cardiovascular risk factors and the extent of atherosclerosis. Patients with TAAs caused by dissection have lipoprotein (a) levels comparable with healthy individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 34 publications
0
25
2
Order By: Relevance
“…Our findings were not in agreement with one previous study, in which it was reported that patients with TAAs (n = 39) caused by AD have Lp(a) levels comparable to healthy individuals [4]. The inconsistent results might be due to the different criteria for inclusion.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Our findings were not in agreement with one previous study, in which it was reported that patients with TAAs (n = 39) caused by AD have Lp(a) levels comparable to healthy individuals [4]. The inconsistent results might be due to the different criteria for inclusion.…”
Section: Discussioncontrasting
confidence: 75%
“…However, to the best of our knowledge, until now, limited data are available on the association of Lp(a) and AD [4]. The aim of this study was to investigate Lp(a) serum levels in patients with AD and in healthy individuals.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…First, we think that it provides the first evidence that a biomarker of ECM degradation is associated with aortic aneurysm location. We could find no previous work on ECM biomarkers showing differences between patients with TAA and AAA, although others have compared lipoprotein-a concentration 23 and concomitant medical conditions 24 between these patient groups. Second, the study sample was derived from an aortic aneurysm registry with standardized procedures for blood and data collection.…”
Section: Odds Ratio (Or)mentioning
confidence: 51%
“…There are few evidences that there may be an association [55,56]. However, more studies are needed in order to define this role.…”
Section: Lipoprotein (A) and Peripheral Vascular Diseasementioning
confidence: 99%